G22(P) Are qi methods useful in the design and delivery of a blended learning programme?. (24th May 2017) - Araujo, R; Oligbu, F; Cleugh, F; Blair, M
Abstract : Background: Six conditions constitute 83% of ED attendances. 1 Up to 40% of GPs have no formal paediatric training. 2 There is minimal evidence that education is effective in changing physician behaviour or patient outcomes. 3 In response, the RCPCH developed 4 e-learning sessions specifically for GPs on: fever, breathlessness, diarrhoea and vomiting and constipation. However, elearning alone is not as effective as a blended learning approach. 4- Quality Improvement (QI) methodologies have rarely been used to deliver such programmes. Aims: Design and evaluate a blended learning educational intervention (e-learning component and a 3 hour face to face workshop) for GPs utilising QI methodologies. Methods: The use of Process Maps and Plan, Do, Study, Act (PDSA) cycles were used to inform and assess delivery. E-learning pre and post tests were done to assess knowledge attainment. Feedback was collected during and at the end of each face to face workshop and GPs invited to participate in a telephone interview 4–6 weeks later. Results: 163 attended the two workshops and 104 completed the feedback. Workshops were rated as 'Very good' or 'Excellent' by 84%; 74% of the attendees reported this was relevant to their current practice. 32 participants completed the e-learning (workshop1: 20%, workshop2: 32%). Average pre/post knowledge test: 6.1/10 and 9.5/10 respectively. E-learning content rated: 4.5 out of 5 (1 poor and 5 excellent). 11 GPs consented to be interviewed; 5 were interviewed 4–6weeks post programme. All GPs reported that the programme has had an impact in their clinical practice e.g. ' I have finally have got round to printing off the traffic light table (…) I can actually look up respiratory rates and heart rates, and that has made a difference, and I actually write them down more often '. Process Mapping and PDSAs identified a number of themes; such as e-learning accessibility, standardised presentation content and interview recruitment (Fig 1). Conclusion: This study demonstrates that QI methods have been invaluable in design and delivery of an educational bundle. The RCPCH have used these findings to deliver a national launch including onsite e-learning completion and workshop in 2017.